Oxford Scholarship Online 2017
DOI: 10.1093/oso/9780190622183.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Concubines on the Road: Ibn Battuta’s Slave Women

Abstract: The chapter considers the enslaved women belonging to Abu Abdallah Muhammad ibn Battuta (1304–1368 CE). Ibn Battuta was a serial slave owner, master of numerous concubines, and author of the renowned Book of Travels (Rihla) completed in 1357. It underscores the ubiquitous use of concubinage during the medieval Islamic period. Drawing on Ibn Battuta’s own observations, the discussion points to the hardships imposed on these women by Ibn Battuta’s relentless itinerary, pointing out that, unlike free women, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The practice of slavery was prevalent in the form of forced migration of hundreds of thousands of people from different regions into mainland Persia. Movement was thus an unavoidable part of slaves' lives, as travel for new slaves in the Islamic world began with the captivity of the slaves after the battles, followed by transportation to slave markets (Tolmacheva 2017). Shah Abbas I (r. 1587-1629) expanded the earlier system of slave raids into the Christian, Georgian, and Armenian regions of the Caucasus and conducted mass resettlements of urban and rural people within Iran and along the empire's borders (Ricks 2001).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…The practice of slavery was prevalent in the form of forced migration of hundreds of thousands of people from different regions into mainland Persia. Movement was thus an unavoidable part of slaves' lives, as travel for new slaves in the Islamic world began with the captivity of the slaves after the battles, followed by transportation to slave markets (Tolmacheva 2017). Shah Abbas I (r. 1587-1629) expanded the earlier system of slave raids into the Christian, Georgian, and Armenian regions of the Caucasus and conducted mass resettlements of urban and rural people within Iran and along the empire's borders (Ricks 2001).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Enslaved women and sex workers often traveled, as they accompanied the soldiers to the battle for moral support (Figueroa 1984). Besides, when the masters traveled, the female domestic slaves were sometimes taken along because the free women could avoid the danger and discomfort by declining to accompany the husband; but the concubine slave's status did not allow such agency (Tolmacheva 2017). Olearius (2006) reported that traders and elite men who traveled a lot also had several wives in different cities, where they stopped during their journeys.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Feminism activists disapproved that the ad positioned a necessity to choose between a dress and a sports uniform and the need to fight to be respected. They also spoke out against the promotion of high physical activity, which can lead to injuries, wear and tear on the body, and problems with the reproductive system 11 . Antifeminists were also very vocal on social media when the video had been published, contributing to over 4k dislikes, negative comments, and even one unsuccessful law suit 2 .…”
Section: Women Empowerment In Russiamentioning
confidence: 99%